2022
DOI: 10.1155/2022/5962571
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Self-Care among Patients with Hypertension in Ethiopia: A Systematic Review and Meta-Analysis

Abstract: Background. Self-care adherence for hypertensive patients is a cornerstone for the control of it and prevention of its complications. However, there are inconsistent findings for self-care adherence of hypertensive patients in Ethiopia. Thus, this systematic review and meta-analysis was done to determine the pooled estimate self-care adherence. Methods. This systematic review and meta-analysis was reported based on the Preferred Reporting Items for Systematic Review and Meta-Analysis guideline. An intensive se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
2
4
1
Order By: Relevance
“…Those participants who added additional salt to the plate were more adherent (P<0.01). In this study, the rate of dietary salt restriction was 40% which is higher than reported from two meta-analysis and systematic review studies which was 34% [32] and 37.3% [33]. However, no data report showed an association with medication adherence.…”
Section: Discussioncontrasting
confidence: 73%
“…Those participants who added additional salt to the plate were more adherent (P<0.01). In this study, the rate of dietary salt restriction was 40% which is higher than reported from two meta-analysis and systematic review studies which was 34% [32] and 37.3% [33]. However, no data report showed an association with medication adherence.…”
Section: Discussioncontrasting
confidence: 73%
“…This nding is supported by previous studies conducted in Ethiopia (12) and Ghana (21,29). Evidence shows that implementation of the Compassionate, Respectful, and Caring (CRC) CRC increases patient satisfaction (30).…”
Section: Level Of Households' Heads Satisfaction With the Cbhi Schemessupporting
confidence: 69%
“…The management of hypertension involves multifaceted strategies that encompass lifestyle modifications and adherence to prescribed medication regimes (Jarari et al, 2015;Ks et al, 2021;Midlöv et al, 2008;Milchak et al, 2006). Despite the critical importance of managing this condition, adherence to hypertension management guidelines by both healthcare providers and patients is less than optimal, leading to significant morbidity and mortality (Adedeji et al, 2015;Drawz et al, 2009;Edmealem et al, 2022;Ibezim et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…From the patient's viewpoint, adherence to hypertension management is influenced by personal beliefs, understanding of the disease, socioeconomic factors, and the perceived complexity of the treatment regime. Studies by Nguyen et al (2017) and Edmealem et al (2022) demonstrate that cultural beliefs, economic constraints, and educational levels significantly impact patient adherence to prescribed management plans (Edmealem et al, 2022;Nguyen et al, 2017). Furthermore, evidence emphasize the role of patient education and health literacy as critical factors in enhancing adherence cannot be understated (Cheng & Chiang, 2015;Crowley et al, 2012).…”
Section: Introductionmentioning
confidence: 99%